Distinctive Features of Raman Spectroscopy of Crude Oils of the Absheron Peninsula - Pashayev, A.M.; Valiyev, N.A.; Asgerov, K.E.; Musayev, A.A.; Mammadov, I.Kh.; Allahverdiyev, K.R.; Sadikhov, I.Z. (Herald of Azerbaijan Engineering Academy, 2023)
Raman spectroscopy provides useful information about hydrocarbon fluid inclusions in crude oils. In particular, the presence or absence of hydrocarbon functional groups may be qualitatively determined. In most oil spills situations, it is desirable to have more than one analytical technique for detecting of spilled oil to its suspected source. In this paper we present first results of Raman scattering spectra of crude oils taken from 6 Oil-gas Production Companies of Azerbaijan Republic.